2008
DOI: 10.1001/archinternmed.2007.70
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Is a Risk Factor for Death in Patients With Stroke

Abstract: Patients with stroke and obstructive sleep apnea have an increased risk of early death. Central sleep apnea was not related to early death among the present patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
185
1
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 306 publications
(207 citation statements)
references
References 26 publications
5
185
1
16
Order By: Relevance
“…Only patients with OSA (AHI >10) had an increased risk of early death. 9 In a prospective study on 161 patients admitted to a stroke unit, no relationships were found between sleep-related respiratory events and the topographic location of the neurologic lesion or vascular involvement. 34 …”
Section: Prevalence Of Obstructive Sleep Apnea In the Poststroke Periodmentioning
confidence: 97%
See 4 more Smart Citations
“…Only patients with OSA (AHI >10) had an increased risk of early death. 9 In a prospective study on 161 patients admitted to a stroke unit, no relationships were found between sleep-related respiratory events and the topographic location of the neurologic lesion or vascular involvement. 34 …”
Section: Prevalence Of Obstructive Sleep Apnea In the Poststroke Periodmentioning
confidence: 97%
“…[31][32][33][34][35] The reported prevalence in the literature is very high, ranging from 40% to 90%, 9,10,34,[36][37][38][39][40] likely reflecting different study designs and definitions of SDB.…”
Section: Prevalence Of Obstructive Sleep Apnea In the Poststroke Periodmentioning
confidence: 99%
See 3 more Smart Citations